2022
DOI: 10.1155/2022/5536266
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Mechanism of Lianhua Qingwen in Treating Influenza Virus Pneumonia and New Coronavirus Pneumonia with the Concept of “Different Diseases with the Same Treatment” Based on Network Pharmacology

Abstract: The 31 main components of Lianhua Qingwen (LHQW) were obtained through a literature and database search; the components included glycyrrhizic acid, emodin, chlorogenic acid, isophoroside A, forsythia, menthol, luteolin, quercetin, and rutin. Sixty-eight common targets for the treatment of novel coronavirus pneumonia (NCP) and influenza virus pneumonia (IVP) were also obtained. A “component-target-disease” network was constructed with Cytoscape 3.2.1 software, and 20 key targets, such as cyclooxygenase2 (COX2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It is generally accepted that the lower the binding of the small molecule ligand to the receptor, the greater the interaction and the greater the potential activity of the component. The binding affinity that is less than -5 kcal/mol indicates spontaneous binding between the small ligand molecule and the receptor protein, while the binding affinity that is less than -7.0 kcal/mol indicates the good binding activity of the ligand to the receptor ( 22 ). According to the molecular docking results ( Table 2 ), we found that the binding affinity between aspirin and TPBG-4cnc, OPRK1-4djh, and RELA-3qxy was less than −5 kcal/mol, indicating that they have certain binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that the lower the binding of the small molecule ligand to the receptor, the greater the interaction and the greater the potential activity of the component. The binding affinity that is less than -5 kcal/mol indicates spontaneous binding between the small ligand molecule and the receptor protein, while the binding affinity that is less than -7.0 kcal/mol indicates the good binding activity of the ligand to the receptor ( 22 ). According to the molecular docking results ( Table 2 ), we found that the binding affinity between aspirin and TPBG-4cnc, OPRK1-4djh, and RELA-3qxy was less than −5 kcal/mol, indicating that they have certain binding activity.…”
Section: Resultsmentioning
confidence: 99%
“…It reveals the relationship between the gut microbiota, intestinal mucosal barrier, and viral pneumonia, and part of the mechanisms of LHQW in the treatment of viral pneumonia. The LHQW capsule, a traditional Chinese medicine compound, has 13 traditional Chinese medicines and many action targets, such as Akt1, P53, Cox-2, and TLR4 (Xia et al, 2020;Su et al, 2022), and has unique advantages in the treatment of influenza virus infection. Formula composition: forsythia suspensa 225 g, honeysuckle 255 g, isatis root 255 g, bitter almond 85 g, menthol 7.5 g, houttuynia cordata 255 g, rhubarb 51 g, patchouli 85 g, Male Fern Rhizome 255 g, Rhodiolae Herba 85 g, Ephedra equisetifolia 85 g, licorice 85 g, gypsum 255 g. Studies have confirmed that the main active ingredients of LHQW are chlorogenic acid, ursolic acid, rutin, luteolin, and quercetin, which exhibit antibacterial activities (Niu et al, 2021;Yang et al, 2021;Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LHQW, combined with routine treatment, can be used as synergistic therapy to significantly improve symptoms and reduce the mortality rate of critically ill patients (Wu et al, 2021;Yang et al, 2021). Animal experiments have also confirmed that LHQW can reduce the viral load in the lungs of mice with viral pneumonia, reduce the expression of inflammatory factors in the lungs, and improve lung injury (Xia et al, 2020;Su et al, 2022). It is well known that viral clearance in the lung depends mainly on lymphocytes and macrophages (Bedi et al, 2022;Cammann et al, 2022;Harris and Borg, 2022;McGee et al, 2022;Verma et al, 2022;Wei et al, 2022;Zhang H. et al, 2022;Zhang M. et al, 2022); however, the present findings do not clarify how LHQW reduces the viral load in the lung and improves lung injury with viral pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Results were exported in tab-separated value (TSV) format, and the unconnected targets were filtered out. Subsequently, visualization of the PPI data was constructed in Cytoscape 3.9.1 [ 26 ]. The topology parameters of the network were analyzed using the Network Analyzer function in Cytoscape 3.9.1.…”
Section: Methodsmentioning
confidence: 99%